2007
DOI: 10.1007/s10787-006-1537-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological profile of ramosetron, a novel therapeutic agent for IBS

Abstract: Ramosetron is a potent and selective serotonin (5-HT)(3) receptor antagonist that has been shown to affect abnormal colonic function and abdominal pain in animals. Ramosetron (0.3 to 100 microg/kg, p.o.) has been found to significantly suppress abnormal defecation induced by conditioned-fear stress (CFS), restraint stress, corticotropin releasing factor (CRF) and 5-HT in rats and mice, and these effects were more potent than those of alosetron, cilansetron or loperamide. On the other hand, ramosetron (3,000 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Although the effects of ramosetron and alosetron on normal defecation in rats were not actually evaluated in these two literature reports, Okano et al (9) reported that alosetron significantly inhibited both novelty stress-induced defecation and normal defecation in Mongolian gerbils. However, we also obtained the data showing that oral administration of ramosetron did not inhibit normal defecation in dogs, whereas tiquizium significantly inhibited it (24). Therefore, we considered that the discrepancy may be attributable to species differences in the roles of 5-HT 3 receptor in normal defecation between rats, dogs, and Mongolian gerbils, although no exact cause is known so far.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although the effects of ramosetron and alosetron on normal defecation in rats were not actually evaluated in these two literature reports, Okano et al (9) reported that alosetron significantly inhibited both novelty stress-induced defecation and normal defecation in Mongolian gerbils. However, we also obtained the data showing that oral administration of ramosetron did not inhibit normal defecation in dogs, whereas tiquizium significantly inhibited it (24). Therefore, we considered that the discrepancy may be attributable to species differences in the roles of 5-HT 3 receptor in normal defecation between rats, dogs, and Mongolian gerbils, although no exact cause is known so far.…”
Section: Discussionmentioning
confidence: 93%
“…In detail, corticotropin-releasing factor secreted in response to stress increases the release of endogenous 5-HT from 5-HT-containing nerves and/ or enterochromaffin cells, resulting in the activation of 5-HT 3 receptors in the enteric nervous system (23). Endogenous 5-HT stimulates the release of various neurotransmitters, such as acetylcholine, via the activation of 5-HT 3 receptors, to induce the acceleration of colonic transit (12) and abnormal water transport (24), which in turn cause abnormal defecation. Our present study showed that the 5-HT 3 -receptor antagonist ramosetron did not affect normal defecation in rats at doses higher than were needed to inhibit CFS-induced defecation, whereas the antimuscarinic agent tiquizium (25) inhibited both CFSinduced and normal defecation at the same dose.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ramosetron inhibited an acceleration of defecation by CRH [2]. On the other hand, it is suggested that ramosetron does not inhibit defecation abnormality induced by prostaglandin and castor oil or spontaneous defecation, but only inhibits acceleration of defecation or diarrhea induced by stress [6, 8, 9]. In addition, ramosetron has been shown to increase the low perceptual threshold of the colon caused by restraint stress in the rats.…”
Section: Introductionmentioning
confidence: 99%
“…A selective 5-HT 3 receptor antagonist, ramosetron, slows colonic transit and reduces pain sensation in animal models subjected to stress (39,40). Ramosetron (5 and 10 μg) was tested in two studies of approximately 1,000 patients with IBS-D and was superior to placebo in global relief of symptoms, with similar efficacy in men and women.…”
Section: Chronic Diarrheamentioning
confidence: 99%